Effect of Daridorexant on the Pharmacokinetics of Midazolam, and on the Pharmacokinetics and Pharmacodynamics of Warfarin in Healthy Male Subjects - Isabelle Zenklusen; Jasper Dingemanse; Christian Reh; Martine Gehin; Priska Kaufmann (Adis, Springer Healthcare, 2024)
Abstract Background and Objectives Daridorexant, a dual orexin receptor antagonist was recently approved for the treatment of insomnia at doses up to 50 mg once per night. This study investigated the effect of single-dose and multiple-dose daridorexant 50 mg at steady state on the pharmacokinetics (PK) of the cytochrome P450 (CYP) 3A4-sensitive substrate midazolam, and the effect of single-dose daridorexant 50 mg on the PK and pharmacodynamics (PD) of the CYP2C9-sensitive substrate warfarin. Methods In this prospective, single-center, open-label, fixed-sequence, phase I, drug-drug interaction study, 18 healthy male subjects sequentially received Treatment A, B, and C in three periods. Treatment A consisted of a single oral concomitant administration of midazolam 2 mg and warfarin 25 mg on day 1 of the first period. Treatment B consisted of one oral administration of daridorexant 50 mg followed 1 h later by a single oral dose of midazolam 2 mg concomitantly with a single oral dose of warfarin 25 mg on day 1 and a once-daily oral administration of daridorexant 50 mg for 6 days of the second period. Treatment C consisted of a single oral administration of daridorexant 50 mg at steady state followed 1 h later by a single oral administration of midazolam 2 mg on day 1 of the third period. Blood samples were assessed for midazolam and S-warfarin PK, and PD (international normalized ratio and factor VII). Noncompartmental  PK parameters and PD variables were evaluated with geometric mean ratios and 90% confidence intervals of Treatment B/A versus C/A for midazolam, and treatment B/A for warfarin. Safety and tolerability of each treatment were also assessed. Results Midazolam maximum plasma concentration (C max) and area under the plasma concentration-time curve from 0 to 24 h (AUC0-24) were 1.13- and 1.42-fold higher, respectively, after single-dose administration of daridorexant 50 mg compared to administration of midazolam alone, while C max and AUC0-24 were 1.12- and 1.35-fold higher, respectively, after administration of daridorexant 50 mg once daily at steady state. Terminal half-life and time to maximum plasma concentration were comparable between treatments. Daridorexant had no influence on the PK and PD of warfarin. All treatments were safe and well tolerated. Conclusions Daridorexant at 50 mg is classified as a weak CYP3A4 inhibitor after single- and multiple-dose administration once daily at steady state. Daridorexant 50 mg did not induce CYP3A4 activity or inhibit CYP2C9 activity. Clinical Trial Registration This trial (NCT05480488) was registered on 29 July, 2022.